Baroclinic energy flux at the continental shelf edge modified by wind‐mixing. Issue 6 (18th March 2015) - R. Stephenson, Gordon; Hopkins, Joanne E.; Mattias Green, J. A.; Inall, Mark E.; Palmer, Matthew R.
Abstract: Temperature and current measurements from two moorings onshore of the Celtic Sea shelf break, a well‐known hot spot for tidal energy conversion, show the impact of passing summer storms on the baroclinic wavefield. Wind‐driven vertical mixing changed stratification to permit an increased on‐shelf energy transport, and baroclinic energy in the semidiurnal band appeared at the moorings 1–4 days after the storm mixed the upper 50 m of the water column. The timing of the maximum in the baroclinic energy flux is consistent with the propagation of the semidiurnal internal tide from generation sites at the shelf break to the moorings 40 km away. Also, the ∼3 day duration of the peak in M2 baroclinic energy flux at the moorings corresponds to the restratification time scale following the first storm. Key Points: Depth‐averaged N governs criticality for first mode internal waves on the shelf Wind‐mixing causes 3 day subcritical window for IT to propagate on‐shelf Peaks in M2 energy flux at shelf moorings are delayed relative to wind‐mixing